Research Trend of Digital Innovation in Banking: A Bibliometric Analysis - Antonius Sony Eko Nugroho; Mohammad Hamsal (Center for Risk Management & Sustainability and RSF Press, 2021)
This paper aims to analyze research trends of Digital Innovation in Banking scientifically through bibliometric studies. Initial data were collected using Publish or Perish from 2011 to 2021 by searching for published papers indexed by Crossref, Google Scholar, Microsoft Academic, and Scopus database. The results show that scientific publications of Digital Innovation in Banking have increased gradually since 2016. The Scopus database is used because it contains journals and conference proceedings deemed more relevant by the academic community with detailed DOIs. VOSviewer and Microsoft excel were used as the tools to analyze co-authorship, co-occurrence, and citation obtained from the Scopus database. The visualization of the research trends of Digital Innovation in Banking resulted in three co-occurrence clusters leading to some of the topic areas mentioned in the results; 1) Digital Innovation in Banking related to the technology implementation and environmental innovations, 2) Digital Innovation in Banking business management in the world, and 3) Digital Innovation in Banking in relating to its effect and benefit to society. Technology is rapidly changing the financial services industry, especially banks. Digital innovation resulting from the use of digital technology will help banking improve customer experience and maintain banking performance. These study findings will help researchers recognize the research trends of Digital Innovation in Banking globally and suggest future research directions.